Northwest animal babies - Wolfe, Art (Sasquatch Books, 1998)
Introduces some of the baby animals found in the Pacific Northwest, including raccoon kits, a bison calf, grey wolf pups, Coho salmon fry, Western Sandpiper chicks, and a cougar kitten.